ANALISIS DOMINASI AKAD IJARAH DALAM OBLIGASI SYARIAH DI INDONESIA - Luqita Romaisyah; Saqofa Nabilah Aini; Riska Agustin (Kompetensi (Competence : Journal of Management Studies), 2023)
Islamic bonds (sukuk) are proof of ownership of tangible assets or investment activities, which funds obtained from the issuance of Islamic bonds are used for purposes in accordance with sharia principles. In Indonesia, there are three types of outstanding Islamic bonds, namely Islamic bonds with ijarah, mudharabah, and wakalah contracts. Among the three types of contracts, ijarah contracts dominate the outstanding Islamic bonds in Indonesia. This study uses qualitative methods with literature study techniques to analyze the causes of ijarah contracts becoming a favorite for issuers and investors, thus dominating the outstanding Islamic bonds in Indonesia. Profits (return) in the form of rental payment (ujroh) with a fixed amount in each period, are the advantages of ijarah Islamic bonds, because they can guarantee certainty of profits received in each period, in any conditions. In addition, the amount of profit that is known at the beginning of the issuance of Islamic bonds, makes it easier for issuers to manage funds originating from the issuance of ijarah Islamic bonds. In essence, ijarah Islamic bonds are more identical and similar to conventional bonds, but there is an underlying asset that makes this transaction halal and does not contain usury. Ijarah Islamic bonds can be an interesting option for risk averse investors who wish to invest in a halal manner.